PENGARUH MODEL TWO STAY TWO STRAY TERHADAPA KEMAMPUAN NUMERASI SISWA KELAS V UPT SPF SD INPRES TAMAMAUNG 1 KECAMATAN PANAKUKANG KOTA MAKASSAR - Inriani, Risna; Ernawati; Hadaming, Hamdana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
RISNA INRIANI, 2025. The Effect of the Two Stay Two Stray Model on the Numeracy Skills of Fifth-Grade Students at UPT SPF SD Inpres Tamamaung 1, Makassar City. Undergraduate Thesis. Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervisor I Ernawati and Supervisor II Hamdana Hadaming. This study aimed to determine the numeracy skills of fifth-grade students at UPT SPF SD Inpres Tamamaung 1 Makassar City after the implementation of the Two Stay Two Stray (TSTS) learning model, as well as to examine the effect of using the TSTS learning model on students’ numeracy skills. This research employed a quasi-experimental method using a pretest–posttest control group design. The population of the study consisted of all fifth-grade students at UPT SPF SD Inpres Tamamaung 1 Makassar City. The sampling technique used was saturated sampling, in which all members of the population were included as research samples. Therefore, all 48 fifth-grade students were involved as the research sample, consisting of Class V A as the experimental class and Class V B as the control class, with 24 students in each class. The research instrument was a numeracy ability test in the form of essay questions administered during the pretest and posttest. The results showed that the average numeracy score of students in the experimental class increased from 53.33 in the pretest to 85.21 in the posttest, while the average score of students in the control class increased from 45.21 to 68.54. These results were strengthened by inferential statistical analysis using an independent samples t-test on the posttest data, which showed a significance value (Sig. 2-tailed) of less than 0.001 with a t-value of 6.819 at a significance level of 0.05 and 46 degrees of freedom. Based on these results, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. It can be concluded that the Two Stay Two Stray (TSTS) learning model has a positive and significant effect on the numeracy skills of fifth-grade students at UPT SPF SD Inpres Tamamaung 1 Makassar City.